Using Teams Games Tournament (TGT) to Increase Students’ Vocabulary Acquisition and Reduce Their Learning Anxiety the Case of Seventh-Grade Students at Junior High School - Mughits Alwi; Hendi Pratama; Henrikus Joko Yulianto (Universitas Islam Negeri Palopo, 2025)
This study focuses on two persistent issues in EFL classrooms, limited vocabulary acquisition and high levels of learning anxiety among seventh-grade students. The researcher examined whether the Teams Games Tournament (TGT) Scramble Game is more effective than traditional instruction in improving vocabulary acquisition while reducing anxiety. Using a mixed-methods, quasi-experimental design with a nonequivalent control group, the study involved 60 students at Junior High School Brebes, divided equally into an experimental group and a control group. Vocabulary achievement was measured through pre-tests and post-tests, while anxiety levels were assessed using the Foreign Language Classroom Anxiety Scale (FLCAS) developed by Horwitz et al. (1986), supported by classroom observations and semi-structured interviews. Quantitative analysis using N-Gain scores showed that the experimental group reached a moderate improvement (62%), which was substantially higher than the control group’s 48%, indicating stronger vocabulary development through TGT. In terms of affective outcomes, students in the experimental group shifted from being “very anxious” to “mildly anxious” or “relaxed,” while anxiety in the control group largely remained high. Qualitative findings further revealed that students perceived the TGT Scramble Game as “fun, motivating, and less stressful,” promoting peer support and active participation. Consistent with cooperative learning theory (Slavin), Thus, the TGT Scramble Game effectively enhances vocabulary learning while creating a low-anxiety classroom environment, offering meaningful implications for student-centered EFL instruction.